Nursing Home COVID-19 Litigation: Regulation vs. Reality. - Swinehart, Amy (Journal of Legal Nurse Consulting)
The COVID-19 pandemic disproportionately impacted the elderly population. This is especially true of elderly in congregate living communities such as nursing homes or long-term care facilities. Nursing homes have long-standing requirements for infection control programs and emergency preparedness plans. Despite these regulations, the United States has seen staggering death tolls among elderly people in nursing homes. This article will provide a broad overview of pre-pandemic regulations, a glimpse into nursing home care's reality during the pandemic, and implications for legal nurse consultants.